Лінгвопоетичне втілення концепту ЖІНКА у поезії Сільвії Плат - Заболотна, Ольга (Видавництво Львівської політехніки, 2017)
The article aims at an overview of the concept WOMAN and its main characteristics in the poetry of Sylvia Plath. Considerable attention is paid to the definition of categories “discourse” and “gender” provided by native and foreign linguists.
Keywords: жіночий дискурс; текст; фемінізм; архетип; жіноча сутність; концепт